Periodismo de agencia: inmediatez, capacidad y adaptación - Veliz Sumoso, Victor Humberto (2023)
The present work to opt for the title of Bachelor of Communication addresses the accumulated experience exercising journalism in the Andean News Agency, the official agency of the Peruvian State, since 2002, the year of its relaunch, to the present. During this period, the agency has gone through extremely important changes, marked mainly by the constant improvement of communication technologies, against which it has had to adapt to continue and maintain validity as an information medium. In the following lines I share my performance as editor of the Regional section and the most difficult coverage of that time: the Pisco earthquake; then the move to Politics and performance in a section sensitive to the events that set the course of the country. Immediacy, adaptability and versatility summarize the spirit of agency journalism practiced at this time. I attach notes, interviews and links that give an account of my performance